2015
DOI: 10.1016/j.jvs.2014.12.050
|View full text |Cite
|
Sign up to set email alerts
|

Role of high shear rate in thrombosis

Abstract: Acute arterial occlusions occur in high shear rate hemodynamic conditions. Arterial thrombi are platelet-rich when examined histologically compared with red blood cells in venous thrombi. Prior studies of platelet biology were not capable of accounting for the rapid kinetics and bond strengths necessary to produce occlusive thrombus under these conditions where the stasis condition of the Virchow triad is so noticeably absent. Recent experiments elucidate the unique pathway and kinetics of platelet aggregation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
183
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(204 citation statements)
references
References 52 publications
2
183
0
4
Order By: Relevance
“…The exact mechanism of mtDNA release in this setting was not investigated. Turbulent flow may have resulted in activation of clotting cascades or lysis of cells [36, 37]. Similarly, endotracheal tube placement in surgery has been associated with higher concentrations of mtDNA in throat lavage fluid.…”
Section: Release Of Cf-mtdna Via Cell Necrosis In Trauma and Surgerymentioning
confidence: 99%
“…The exact mechanism of mtDNA release in this setting was not investigated. Turbulent flow may have resulted in activation of clotting cascades or lysis of cells [36, 37]. Similarly, endotracheal tube placement in surgery has been associated with higher concentrations of mtDNA in throat lavage fluid.…”
Section: Release Of Cf-mtdna Via Cell Necrosis In Trauma and Surgerymentioning
confidence: 99%
“…Shear rates higher than 5000 s −1 are considered as pathological and shear rates higher than 8000-10 000 s −1 activate von Willebrand Factor. 14,21 Therefore, all shear rates above 10 000 s −1 are considered as relevant. The CTA scale computational model showed an elevated shear rate downstream of the stenosis, which was a result of inertial forces in the curved section after the stenosis.…”
Section: Computational Fluid Dynamics On the 3d Vessel Geometriesmentioning
confidence: 99%
“…It has been shown that shear rate is very important in von Willebrand factor activation and thus influences platelet adhesion and aggregation. 14,15,20,21 However, due to inherent limitations posed by 2D wafer-based microfabrication techniques of microfluidic chips, the channels in almost all onchip thrombosis models inevitably possess planar configurations with rectangular cross-sections instead of the typical 3D, round cross-section blood vessel structures found in vivo. 11,22 A number of strategies have been employed to produce chips that contain microfluidic channels with circular cross-sections.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, discrepancies may be attrib- 16 Moreover, high shear rates cause explosive platelet thrombosis associated with life-threatening hemorrhage or arterial occlusion. 17 Even though attempts have been made to improve the hemodynamic characteristics of coronary artery bypasses, 18 the performance of the resulting configurations remains controversial.…”
Section: Study Limitationsmentioning
confidence: 99%